Pengembangan Bahan Ajar Berbasis Ensiklopedia Ilmu Pengetahuan Sosial Pada Materi Kegiatan Ekonomi Untuk Meningkatkan Hasil Belajar Siswa SD NU Insan Cendekia Ngadiluwih Kediri - Salsabila Aida Hasya; Agus Purwowidodo (Gerasi Insan Nusantara, 2024)
This research aims to develop and obtain encyclopedia-based teaching materials. The type of research used is research and development with the ADDIE development model. The aim of this research is to determine Social Sciences learning on economic activity material, determine the development of encyclopedia-based teaching materials, and determine student learning outcomes after using encyclopedia-based teaching materials on economic activity material. The results of the validation of teaching material products from material expert 1 obtained a score of 95%, meaning valid, material expert II 75% with quite valid qualifications, teaching material design expert 75%, meaning quite valid, and learning experts got a score of 85% with valid qualifications. . The results of the questionnaire assessment in the small group test obtained a score of 93% and the large group test was 94% and both were valid. The results of data analysis show that tcount is greater than ttable, namely in post test I tcount = 8.360, in post test II tcount = 9.272 and ttable = 2.069. The significance level in post test I = 0.588 ≥ 0.05, in post test II = 0.463 ≥ 0.05. So learning with the product being developed can be said to be effective.